Reimagining urban Marxisms : rethinking thinkers, texts and challenges - Biagi, Francesco, 1986- (Critiques and alternatives to capitalism, 2025)
"This volume presents an interdisciplinary and international revaluation of urban Marxisms. Bringing together the main critical Marxist perspectives from around the world on contemporary urban studies, it engages with a range of issues connected to the 'urban question', such as urban sprawl, housing and increasing rates of urbanization across the globe. With attention to the manner in which the three axes of class, gender and race play a fundamental role in contemporary social phenomena, it interweaves different issues that are inextricably linked in matters of urban inequality. The book bridges a significant gap between urban studies and Marxists theories by reviving Marx and Engels' ideas in the context of analyzing urban studies in the twenty-first century. The objective is to bring together diverse perspectives and directions of the ongoing debate on the "urban question". Although there are multiple Marxisms and theoretical currents inspired by Marxism that seek to understand the urban and spatial transformations of today, there has been a lack of comprehensive scholarship that systematically brings them together to frame this debate. The goal is to unite the main critical Marxist perspectives on contemporary urban studies. Reimagining Urban Marxisms will therefore appeal to scholars across disciplines with interests in Marxist analyses of contemporary urban and spatial transformations, and the phenomenon of planetary urbanization"--